PENINGKATAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR BIOLOGI MENGGUNAKAN METODE INKUIRI TERBIMBING DISERTAI LKS PADA SISWA KELAS X.2 SMA MUHAMMADIYAH 2 METRO TAHUN PELAJARAN 2011/2012 - Rika Masyitoh; Handoko Santoso (Bioedukasi Jurnal Pendidikan Biologi, 2012)
The biology learning emphasizes providing learning experiences directly, ideally be studied scientifically so that the students are directly involved in finding his own understanding. Lack of science process skills students' low trigger. The purpose of this research is to improve science process skills and the results of biological studies using guided inquiry method with LKS in X.2 graders SMA Muhammadiyah 2 Metro, amounting to 22 students. This study is a Classroom Action Research (CAR) with two cycles each consisting of three sessions. Science process skills of students has increased from cycle I to cycle II of 11.1% for the skills of observation, 9% for classifying skills, communicating skills 9.1% to 13.2% for the skill and conclude. Data on students' pre-PTK into the cycle I increased 13.61% and 18.2% in cycle II. From the results of these studies suggest that the teacher researchers to apply these methods in teaching science, especially biology. Kata Kunci: inkuiri terbimbing disertai LKS, keterampilan proses sains,  hasil belajar.